KOMPETENSI GURU ILMU PENGETAHUAN SOSIAL (IPS) MTs NEGERI BARABAI - Siti Fatimah (JURNAL SOCIUS, 2013)
The issue of this study is how is the competence of Social Studies Teachers at MTsN Barabai. This research objective is to describe the pedagogic competence, personal competence, professional competence, and social competence of social studies teachers at MTsN Barabai. The method of this study used descriptive qualitative approach, describing the competence of social studies teachers of MTsN Barabai: the pedagogic competence, personal competence, professional competence, and social competence.  Data in this study were collected by using (1) questionnaires, (2) observation, (3) interview, and (4) documentation. This study did not use a sample, it means that all population of social studies teachers is involved to be investigated (total sampling). The result of the study showed that pedagogic competence of social studies teachers at MTsN Barabai is 3. 28 or 82. 00 categorized into good criteria. Personal competence is 3. 54 or 88.50 categorized into good criteria. Profesional competence is 2. 98 or 74. 50 categorized into sufficient criteria and for social competence is 3. 17 or 79. 25 categorized as good criteria. Therefore, it can be concluded that the competence of social studies teachers at MTsN Barabai is 3. 24 or 81. 00  which is categorized into good criteria. In order to improve teachers’ competence, social studies teachers of MTsN Barabai are suggested to improve their educational qualification by taking part in training activities. Key Words : Competence of Teachers, Social Studies.